SISTEM TERINTEGRASI PORTAL WEB PERGURUAN TINGGI AGAMA ISLAM NEGERI MENGGUNAKAN METODE GRABBING - Sumarsono Sumarsono; Ahmad Syihab Husin (Kaunia: Integration and Interconnection Islam and Science, 2013)
Website is one of the tools used State Islamic University to facilitate and share information - their current information. However, with so many websites makes the user (users) difficult to obtain such information at a time. Users are required to open the website one by one which takes quite a long time.This study uses web grabbing technique or what is often referred to as web scrapping / web fetching, the technique of taking content from a server or website and display it in the system. In its implementation, the system uses the PHP cURL library which is used to retrieve the content of the website. Integrated web portal system is able to retrieve contents the latest information of website and be able to display it back on the system without need to enter or change the data. This system is very useful for users who need the latest informations.